Determination of radioactivity levels of Norm in freshwater vfish from disused tin-mining pool in Kampar - 302262 Ow, Shin Tsyr; Noorddin Ibrahim,lcsuprvisor; Fakulti Sains (2005)
Project Paper (Sarjana Muda Sains (Fizik Kesihatan)) - Universiti Teknologi Malaysia, 2005